The risk of metabolic syndrome in women with previous GDM in a long-term follow-up. (1st November 2016) - Hakkarainen, Heidi; Huopio, Hanna; Cederberg, Henna; Pääkkönen, Mirja; Voutilainen, Raimo; Heinonen, Seppo
Abstract: The aim of this study was to evaluate the incidence of metabolic syndrome (MetS) during long-term follow-up of women with gestational diabetes (GDM). Furthermore, we evaluated the glycemic measures from an oral glucose tolerance test (OGTT) during pregnancy as predictors of incident MetS. Women diagnosed with GDM were divided into two groups according to the results of OGTT: one abnormal value = GDM1 ( n  = 338) and two abnormal values = GDM2 ( n  = 151), while women with normal glucose tolerance ( n  = 385) served as controls. MetS and its components were evaluated in a follow-up study (mean follow-up time 7.3 ± 5.1 years) according to the International Diabetes Federation (IDF) criteria. Fasting plasma glucose in OGTT was the best predictor of incident MetS in ROC (area under the curve) analysis. The incidence of MetS during a <5-year follow-up was 22.2% in controls, 39.3% in GDM1 and 60.4% in GDM2; and >10-year follow-up 24.2%, 46.2% and 62.5%, respectively. In controls and GDM2, the incidence of MetS remained nearly constant during the follow-up, whereas in GDM1 it increased. In conclusion, already mild gestational glucose intolerance may progress to MetS and therefore merits intervention measures to prevent future cardiovascular disease.